Symposium on Integrated Circuits and Systems Design
DOI: 10.1109/sbcci.2001.953026
|View full text |Cite
|
Sign up to set email alerts
|

On designing mixed-signal programmable fuzzy logic controllers as embedded subsystems in standard CMOS technologies

Abstract: A digitallyprogrammable analogue Fuuy Logic Controller (FLC) is presented. Input and output signals are processed in the analog domain whereas the parameters of the controller are stored in a built-in digital memory. Some new functional blocks have been designed whereas others were improved towards the optimisation of the power consumption, the speed and the modularity while keeping a reasonable accuracy, as it is needed in several analogue signal processing applications. A nine-rules, two-inputs and one-outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The main idea behind using a fuzzy logic controller (FLC) is to establish a model to manage the under control process without needs to mathematical model. It is shown that a fuzzy based approach can result in a better performance and/or simpler implementation, when applied to a complicated or ill-defined process and application [1]. To realize fuzzy logic controller, two common methods are available: software and hardware.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main idea behind using a fuzzy logic controller (FLC) is to establish a model to manage the under control process without needs to mathematical model. It is shown that a fuzzy based approach can result in a better performance and/or simpler implementation, when applied to a complicated or ill-defined process and application [1]. To realize fuzzy logic controller, two common methods are available: software and hardware.…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, analog approach is preferable because of its high speed, low power consumption, low area occupation and less complexity compared with its digital counterpart. The attractiveness of analog circuits for implementing fuzzy hardware lays in its intrinsic compatibility with the fuzzy logic and the needlessness of analog to digital (A/D) and digital to analog (D/A) converters for interfacing sensors and actuators [1]. Comparing with digital implementation, apart from reconfigurability, the main disadvantage of analog realization is its lower accuracy, which is acceptable because of inherent approximate of fuzzy logic.…”
Section: Introductionmentioning
confidence: 99%
“…In the fuzzy systems there are three main steps: 1) fuzzification (membership function generation), 2) fuzzy inference or fuzzy rule evaluation, and 3) defuzzification. Excellent tutorial overviews on a utility of a fuzzy system and its application have been reported in many articles [6]. In the second part of the FLC, the minimum and maximum operators are used to define the sentence connectives.…”
Section: Introductionmentioning
confidence: 99%